2013
DOI: 10.1186/1479-5876-11-124
|View full text |Cite
|
Sign up to set email alerts
|

Mild therapeutic hypothermia is superior to controlled normothermia for the maintenance of blood pressure and cerebral oxygenation, prevention of organ damage and suppression of oxidative stress after cardiac arrest in a porcine model

Abstract: BackgroundMild therapeutic hypothermia (HT) has been implemented in the management of post cardiac arrest (CA) syndrome after the publication of clinical trials comparing HT with common practice (ie, usually hyperthermia). Current evidence on the comparison between therapeutic HT and controlled normothermia (NT) in CA survivors, however, remains insufficient.MethodsEight female swine (sus scrofa domestica; body weight 45 kg) were randomly assigned to receive either mild therapeutic HT or controlled NT, with fo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
25
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 30 publications
(27 citation statements)
references
References 15 publications
1
25
0
1
Order By: Relevance
“…However, animal studies have confirmed that TH protected postresuscitation heart and brain by decreasing oxidant stress, inflammation, and apoptosis. Earlier, Ostadal et al [33] demonstrated that HT produced cardiac protection through the suppression of oxidative stress following CA. Recently, another two studies demonstrated that TH protected post-CPR heart and brain by reducing the expression of inflammatory cytokines and cell apoptosis [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…However, animal studies have confirmed that TH protected postresuscitation heart and brain by decreasing oxidant stress, inflammation, and apoptosis. Earlier, Ostadal et al [33] demonstrated that HT produced cardiac protection through the suppression of oxidative stress following CA. Recently, another two studies demonstrated that TH protected post-CPR heart and brain by reducing the expression of inflammatory cytokines and cell apoptosis [28, 29].…”
Section: Discussionmentioning
confidence: 99%
“…According to animal studies [9-13], early induction of MTH is supposed to be beneficial, but clinical trials did not prove it consistently yet [14-17]. Consequently, earliest possible induction of MTH is emphasized in some recent protocols using nasopharyngeal evaporative cooling and peripheral veno-arterial extracorporeal membrane oxygenation (ECMO) hoping to improve the neurological outcome [18-22].…”
Section: Introductionmentioning
confidence: 99%
“…BAP was also evaluated in the serum of animals receiving MTH in a porcine model of CA, but no significant difference was found [12]. The BAP provides a global measurement of many enzymatic and nonenzymatic antioxidants together, indistinctly.…”
Section: Discussionmentioning
confidence: 99%
“…MTH also prevents damage to other tissues, including the myocardium, liver, and kidney [12]. Damage protection by MTH is reinforced by studies demonstrating reduced oxidative damage after treatment [1113].…”
Section: Introductionmentioning
confidence: 99%